Dielectric, electrical transport and magnetic properties of Er3+substituted nanocrystalline cobalt ferrite. (November 2016) - Kakade, S.G.; Kambale, R.C.; Kolekar, Y.D.; Ramana, C.V.
Abstract: Erbium substituted cobalt ferrite (CoFe2− x Er x O4 ; x =0.0–0.2, referred to CFEO) materials were synthesized by sol-gel auto-combustion method. The effect of erbium (Er 3+ ) substitution on the crystal structure, dielectric, electrical transport and magnetic properties of cobalt ferrite is evaluated. CoFe2− x Er x O4 ceramics exhibit the spinel cubic structure without any impurity phase for x ≤0.10 whereas formation of the ErFeO3 orthoferrite secondary phase was observed for x≥ 0.15. All the CFEO samples demonstrate the typical hysteresis ( M – H ) behavior with a decrease in magnetization as a function of Er content due to weak superexchange interaction. The frequency ( f ) dependent dielectric constant ( ε′) revealed the usual dielectric dispersion. The ε′–f dispersion ( f =20 Hz to 1 MHz) fits to the modified Debye's function with more than one ion contributing to the relaxation. The relaxation time and spread factor derived are ∼10 −4 s and ∼0.61(±0.04), respectively. Electrical and dielectric studies indicate that ε′ increases and the dc electrical resistivity decreases as a function of Er content ( x≤ 0.15). Complex impedance analyses confirm only the grain interior contribution to the conduction process. Temperature dependent electrical transport and room temperature ac conductivity ( σ ac ) analyses indicate the semiconducting nature and small polaron hopping. Highlights: Er 3+ substituted CoFe2 O4 were synthesized with controlled size and morphology. Impedance results confirm the grain contribution to the conduction process. Er 3+ ion enhances the dielectric constant. Small polaron conduction is evident in ac conductivity and dc resistivity. Magnetic and dielectric studies show the potential of electromagnetic applications.